PENGARUH LATIHAN TRANSFER KONTRALATERAL TERHADAP KEMAMPUAN SHOOTING PADA PEMAIN FUTSAL KLUB RED FOX KOTA MALANG - Ony I Gusti; Supriyadi Supriyadi; Mulyani Surendra (Universitas Negeri Malang, 2017)
ABSTRACT: Futsal is a sport that is played by two groups whose aim is to put the ball into the opposing group's goalpost. Contralateral transfer is the transfer of skills from one side of the body to the others (for example, the skill of the left hand is transferred to the right hand). Contralateral transfer is used to increase the mastery of ball kicking skill of non-dominant feet. The results of this study showed that the data before given the treatment had the lowest score of 11 and the highest score of 19. Moreover, each player had an average score of 14,60 with a total number of 15 players. Based on the results of this study, it can be concluded that there is an effect of contralateral transfer exercise towards the ball kicking skill using non-dominant feet on the players of Red Fox Futsal Club Malangcity.Keywords: Futsal, Contralateral Transfer, Shooting